From movement analysis to the construction of a specific muscular strengthening method for alpine skiers - Roux, F.; Buttafoghi, L. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
The muscular strengthening process used by the skiers of the French Federation is generally inspired by weight lifting and athletics schools. Mostly aimed at reinforcing the inferior limbs, this activity is added up to a systematic strengthening of the trunk muscles in order to improve the skier's capacity to keep his posture under acceleration strain.